Adult Neural Stem Cell Regulation by Small Non-coding RNAs: Physiological Significance and Pathological Implications - Penning, Amber; Tosoni, Giorgia; Abiega, Oihane; Bielefeld, Pascal; Gasperini, Caterina; De Pietri Tonelli, Davide; Fitzsimons, Carlos P.; Salta, Evgenia (Frontiers in Cellular Neuroscience, 2022)
The adult neurogenic niches are complex multicellular systems, receiving regulatory input from a multitude of intracellular, juxtacrine and paracrine signals and biological pathways. Within the niches, adult neural stem cells (aNSCs) generate astrocytic and neuronal progenies, with the latter predominating in physiological conditions. The new neurons generated from this neurogenic process are functionally linked to memory, cognition and mood regulation, while much less is known about the functional contribution of aNSC-derived newborn astrocytes and of adult-born oligodendrocytes. Accumulating evidence suggests that the deregulation of aNSCs and their progeny can impact, or can be impacted by, ageing and several brain pathologies, including neurodevelopmental and mood disorders and neurodegenerative diseases, and also by insults, such as epileptic seizures, stroke or traumatic brain injury. Hence, understanding of the regulatory underpinnings of aNSC activation, differentiation and fate commitment could help identify novel therapeutic avenues for a series of pathological conditions. Over the last two decades small non-coding RNAs (sncRNAs) have emerged as key regulators of NSC fate determination in the adult neurogenic niches. In this review, we synthesize prior knowledge on how sncRNAs, such as microRNAs (miRNAs) and piwi-interacting RNAs (piRNAs), may impact NSC fate determination in the adult brain and we critically assess the functional significance of these events. We discuss the concepts that emerge from these examples and how they could be used to provide a framework for considering aNSC (de)regulation in the pathogenesis and treatment of neurological diseases.